1971
DOI: 10.2337/diab.20.11.756
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in the Pima Indians: Evidence of Bimodality in Glucose Tolerance Distributions

Abstract: Venous plasma glucose levels two hours after a 75 gm. carbohydrate load were determined on over 2,900 Pima Indians, a population known to have an extremely high prevalence of diabetes mellitus. In each sex and in each decade above twenty-five years of age, the frequency distributions of the logarithms of the glucose levels were clearly bimodal, but below this age a single symmetrical unimodal distribution was found. A maximum likelihood procedure was used to derive the best fitting theoretical gaussian distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 0 publications
5
58
0
Order By: Relevance
“…Bimodality of fasting and 2-h post-load plasma glucose distributions have been demonstrated in both populations [52][53][54]. The cut-off plasma glucose values between the two modes were: fasting approximately 140 mg/dl (7.8 mmol/l) and 2 h approximately 200 mg/dl (11.1 mmol/1) respectively.…”
Section: Other Facets Of Epidemiological Studiesmentioning
confidence: 99%
“…Bimodality of fasting and 2-h post-load plasma glucose distributions have been demonstrated in both populations [52][53][54]. The cut-off plasma glucose values between the two modes were: fasting approximately 140 mg/dl (7.8 mmol/l) and 2 h approximately 200 mg/dl (11.1 mmol/1) respectively.…”
Section: Other Facets Of Epidemiological Studiesmentioning
confidence: 99%
“…3). The diagnostic cut-point of 11.1 mmol/l (200 mg/dl) for the 2h-PG concentration was originally adopted as the bimodality in Pima Indians [69] and Nauruans [70]. It suggested that a plasma glucose concentration of approximately 11.1 mmol/l best represented the point separating the two components of the frequency distribution.…”
Section: New Diagnostic Criteria For Glucose Intolerancementioning
confidence: 99%
“…The determination of diagnostic cut-points which gave rise to the earlier NDDG [2] and WHO [31] recommendations were based on studies which showed bimodality of both fasting and 2h-PG in the Pima Indians [69] and Nauruans [70] (Fig. 3).…”
Section: New Diagnostic Criteria For Glucose Intolerancementioning
confidence: 99%
“…The population frequency distribution of fasting glucose, oral glucose tolerance results, and HbA1c ** (glycosylated haemoglobin) show bimodal distributions in populations with a high prevalence of diabetes (Figure 1). [16][17][18] The two * In the oral glucose tolerance test (OGTT), 75 g of glu-…”
Section: Objectively Diagnosing Diabetesmentioning
confidence: 99%
“…Such data were used to conclude that diabetes should be diagnosed when the plasma glucose two hours after an oral glucose load, irrespective of age, exceeded 200mg/dl (11.1mmol/L). [16][17][18] 18 When a population is surveyed for glucose values, a wide range of values is detected. In the Pima Indian population with a high prevalence of the disease, the frequency of values is best summarised by two normal distributions rather than one.…”
Section: 10mentioning
confidence: 99%